2021
DOI: 10.1111/imj.15274
|View full text |Cite|
|
Sign up to set email alerts
|

Australia's problem with obtaining consent for psychotropic use in older people

Abstract: Frequent use of psychotropic medicines in people with dementia is a significant concern globally, doing this without informed consent is a violation of human rights, ethics and law. Capacity Australia piloted an intervention to address several hypothetical barriers to obtaining consent for psychotropic use in aged care and has developed a suite of resources to improve rights and health literacy for clinicians, patients and community alike.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…When a person cannot give their own consent, a legally defined substitute decision-maker, such as the person responsible, attorney, or guardian, needs to provide consent. Informed consent cannot be provided by staff members, allied health professionals, or the provider on behalf of the person [ 49 – 51 ]. Psychotropic medication has a history of use in the treatment of dementia behaviours within residential aged care in Australia [ 13 , 52 ] and in other countries [ 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When a person cannot give their own consent, a legally defined substitute decision-maker, such as the person responsible, attorney, or guardian, needs to provide consent. Informed consent cannot be provided by staff members, allied health professionals, or the provider on behalf of the person [ 49 – 51 ]. Psychotropic medication has a history of use in the treatment of dementia behaviours within residential aged care in Australia [ 13 , 52 ] and in other countries [ 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Psychotropic medication has a history of use in the treatment of dementia behaviours within residential aged care in Australia [ 13 , 52 ] and in other countries [ 53 55 ]. Some of this history includes the use of antipsychotics, without consent from the family, next of kin, or those holding power of attorney [ 7 , 19 , 51 , 56 ]. Relatives of people living with dementia in Australian residential aged care homes are documented as expressing their frustrations to learn that psychotropics were administered without their knowledge [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results, together with our examination of antipsychotic persistence among individuals in whom therapy was newly commenced, suggests that most older people with dementia taking an antipsychotic are treated for >90 days. This practice did not align with local recommendations during the study period, 42 nor current guidelines 20 that recommended initial treatment not exceed 12 weeks when antipsychotics are used for managing the behavioral and psychological symptoms of dementia. We also found that prior antipsychotic use was strongly associated with higher incidence of prolonged use in both cohorts, and little geographical and PRAC facility variation was observed.…”
Section: Discussionmentioning
confidence: 96%
“…Prime amongst these is a failure to respect autonomy, manifested by failure to obtain consent (including substitute consent where appropriate) prior to the administration of chemical restraint. Again, this is longstanding [6][7][8]. Notably, there is both anecdotal and research evidence that family members who are designated or default decision makers are neither consulted in regard to consent for chemical restraint [8], nor informed about major side effects including mortality risk, while often subject to pressure by Residential Aged Care Facilities (RACFs) to accede to such restraint [8,9] for fear of the resident with Changed Behaviours losing tenure in the facility.…”
Section: Introductionmentioning
confidence: 99%